Management of soil fertility through application of fertilizers - Kihara, Job Maguta; Bekunda, Mateete A.; Chimonyo, Vimbayi Grace Petrova; Kimaro, Anthony A.; Kotu, Bekele Hundie; Lyimo, Stephen; Mhango, Wenzi (CAB International, 2022)
This chapter presents technologies for replacing the nutrients lost from cropped fields with external fertilizer sources in a manner that minimizes the consequences of too little or too much application. The technology of using industrial fertilizers, organic fertilizers, and application of farmyard manure and compost alone or in combination with industrial fertilizers are discussed in detail.